A Wireless Local Positioning System Concept and 6D Localization Approach for Cooperative Robot Swarms Based on Distance and Angle Measurements - Geiß, Johanna; Sippel, Erik; Gröschel, Patrick; Hehn, Markus; Schütz, Martin; Vossiek, Martin (IEEE Access, 2020)
In wireless sensor networks, spatially distributed nodes provide location-dependent sensorinformation. Therefore, knowledge about the 3D position of all nodes is crucial for the numerous appli-cations that require autonomous mobility. Furthermore, to acquire the nodes’ poses and the complete 6Dnetwork constellation, the 3D orientation of each node is also required. While many theoretical localiza-tion concepts exist for wireless sensor networks, there is still a lack of reliable system and localizationconcepts which enable robust real-time tracking in real-world scenarios. Therefore, we present a systemapproach based on an advanced 24 GHz wireless local positioning system, providing distance and anglemeasurements between pairs of nodes. Furthermore, an extended Kalman filter based localization algorithmis proposed, which evaluates these measurements to track the time varying 6D poses of all nodes inthe network. Because only relative measurements are available, one node is chosen to define a jointnavigation system. Hence, the proposed system works without any previously installed infrastructure orprior information of the network. The system and localization algorithm are validated by measurementsperformed in a mobile wireless sensor network comprising six nodes in an indoor scenario with strongmultipath propagation. However, despite the challenging environment, the system allows for a stable andaccurate 6D pose estimation of all robots in the network with 3D positioning root mean square errorsof 6 to 15 c